RESILIENSI DITINJAU DARI PERSEPSI TERHADAP DU SOSIAL DAN LOCUS OF CONTROL INTERNAL TERHADAP REMAIN VANG BROKEN HOME - Hartini, Sri; Mentari, Sabrini; -, Nurvica; Elvinawanty, Rianda; Khohiro, Kimiko (unprimdn.ac.id, 2023)
This study aims to determine the relationship between resilience with perceptions of social support and internal locus of control. The hypothesis proposed in this study is that perceptions of social support and internal locus of control affect resilience. This study uses multiple regression analysis through the help of SPSS 17 for Windows. It is concluded that there is a positive and significant relationship between perceptions of social support and resilience in adolescents who are in broken homes in Medan City, which can be proven by the results of multiple regression analysis with a value (r) of 0.801, (e) of 0.612 with a significance level of 0.000 (P <0.05). This shows that the predictor of perception of postal support shows that if the score of perception of social support increases by 0.048 units, then resilience also increases by 0.048 units. The predictor of internal locus of control shows that if the locus of control score increases by 0.832, resilience also increases by 0832 units. It can be used as a predictor to predict resilience with the contribution given by perceptions of social support and internal locus of coeternal adolescents who are broken home by 64.20%. Moreover, the results of this study can conclude that the significant hypothesis is that there is a relationship between perceptions of social support and maternal locus of control with the resilience of broken home adolescents.